Cell-free synthesis of leaf protein: Identification of an apparent precursor of the small subunit of ribulose-1,5-bisphosphate carboxylase - Cashmore, A. R. (1978)
Cytoplasmic mRNA has been isolated from the leaves of pea seedlings. Translation of this RNA in the wheat germ cell-free system produces two major products, RI and RII, with molecular weights of 33,000 and 20,000, respectively. Both of these products are considerably larger than the small subunit of ribulose-1,5-bisphosphate carboxylase [3-phospho-D-glycerate carboxy-lyase (dimerizing), EC 4.1.1.39], which is the major product of cytoplasmic protein synthesis in vivo and has a molecular weight of 14,000. Antiserum prepared against the small subunit of ribulose-1,5-bisphosphate carboxylase precipitates from the cell-free products, in 2-3% yield, three polypeptides of molecular weights 18,000, 16,000 and 14,000. The smallest of these polypeptides is indistinguishable, by sodium dodecyl sulfate/polyacrylamide gel electrophoresis, from the small subunit of ribulose-1,5-bisphosphate carboxylase. Although the cell-free product RII is not precipitated with antiserum prepared against the small subunit of ribulose-1,5-bisphosphate carboxylase, the two polypeptides do show extensive sequence homology, as indicated by ion exchange chromatography of their tryptic peptides. The production of RII can also be achieved in a polysome-primed cell-free system, where protein synthesis is restricted to the completion of polypeptide chains that have already been initiated in vivo. These results indicate that RII is apparently a precursor of the small subunit of ribulose-1,5-bisphosphate carboxylase. We suggest that the selective transport of cytoplasmically synthesized organelle proteins, like animal secretory proteins, may be achieved via the production of precursor polypeptides.